Effects of different particle size of rapeseed and linseed in fattening lamb diets. II. Yield of slaughter by-products - Janicki B.; Borys B.; Borys A.; Borzuta K. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The effects of feeding rapeseed and linseed (10% of the diet, 2:1 ratio) and their form (whole, or 50 or 100% ground) in intensive fattening of lambs to 30-35 kg body weight on the yield of slaughter by-products were investigated. No statistically significant effect on the yield of slaughter by-products resulting from fattening lambs with rapeseed and linseed, or from the form of these, was found, except for an increased proportion of perirenal fat. Small and rather unspecific differences were observed in the weight of digesta and weight of the urogenital duct, which require further study. Commercial crossbreeding of prolific sheep with Texel rams did not result in significant differences in the yield of lamb slaughter by-products, with a tendency in crossbreds for lighter body conformation (with the head and legs representing a lower proportion) and lower fatness inside the abdominal cavity (intestinal and perirenal fat).
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)